Compensator design for the Kirchoff plate model with boundary control - Hendrickson, Erik (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a compensator design problem in optimal control theory. An algorithm is developed to compute a finite-dimensional compensator based on the Kalman filter theory. The algorithm is implemented using a standard finite element scheme applied to a Kirchoff plate model with boundary control and boundary observation. Convergence of feedback and compensator gains is examined.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka